KUMPULAN CARITA PONDOK PANGGUNG WAYANG - Suryana Saputra, Roni (2014)
The thesis was intended to describe the structure of the short story, the characters' psychological aspects, the relationship among aspects in the complete stories, and the relationship among psychological aspects with structures of the stories. It used structuralism and psychological literature approach which assumed that literary works were constructed by structures that supported and completed each other, and literary works frequently showed psychological phenomena experienced by the characters. The method employed was descriptive method. It used literature reviews and document analysis technique. It was then found out that (1) the theme raised in the collection of short stories were mostly about daily life such as cultural issues, love, social condition, responsibility, mystic, mystery, and household, (2) the plot illustrated was progressive and "bobok tengah", (3) the character of the stories indicated a woman who was envious, sensitive, autonomous, responsible, and full of love, while the man character was described as a selfish person, dictator, full of jealous, emotional, irresponsible, and exploded his desire. The characters illustrated in the short stories used expository and dramatic technique, (4) the setting shown condition in towns, villages, housing complex, and nature. The social condition illustrated were mostly about individuals with high-social status, poor, educated, and had firm jobs, (5) most titles in the collection were connotative, not in the true meaning, and needed to be meant and interpreted more, (6) the point of view used the third person point of view and the first person point of view, (7) the figure of speech mostly used terms, methapore, hyperbolic, personification, metonim, periphrase, and euphemism (8) psychological aspects indicated stimulus response which constructed characters and their characteristics conditioned by the environment.